Answers

The Brainliest Answer!
2014-04-24T13:06:37+05:30
Given equation of circle is x^2+y^2-2x-4y+5 = 0
equation of tangent is 3x-y+c = 0
now the distance of the tangent from the centre of the circle= radius of circle
for a circle x^2 +y^2 +2gx +2fy +c=0 , the centre is (-g,-f) and radius is (f^2 +g^2-c)^1/2
distance of a line(ax+by+c=0) from a point (x1,y1) is | ax1+by1+c | / (a^2+b^2)^1/2
therefore just substitute the value of the centre (1,2) of the circle in the above equation and equate it to the radius (10)^1/2
we get |1+c|=10
implies c=+9 or  c=-11
1 5 1